The division of labour in the social sciences versus the politics of metaphysics. Questioning Critical Realism's interdisciplinarity - Van Bouwel, Jeroen (Graduate Journal of Social Science, 2006)
Some scholars claim that Critical Realism promises well for the unification of the social sciences, e.g., Unifying social science: A critical realist approach in this volume. I will first show briefly how Critical Realism might unify social science. Secondly, I focus on the relation between the ontology and methodology of Critical Realism, and unveil the politics of metaphysics. Subsequently, it is argued that the division of labour between social scientific disciplines should not be metaphysics-driven, but rather question-driven. In conclusion, I will therefore defend a question-driven pluralism as a guide for interdisciplinarity.